Investigating the SUMOylation and transcriptional regulation of Nurr1 and the splice variant Nurr-1a - Edey, Jade (2023)
Nuclear receptor-related 1 protein (also known as Nurr1 or NR4A2) is an orphan nuclear receptor with multiple roles in many different tissues and pathological settings. It is most commonly known for its vital role in the development, maintenance and survival of dopaminergic (DA) neurons throughout the midbrain, particularly in the substantia nigra (Jankovic et al., 2005). Nurr1 also has a reported role in inflammatory cells such as microglia and macrophages, where it is suggested to dampen down the inflammatory response to prevent excessive inflammation (Lallier et al., 2016, Smith et al., 2015). This reduction in inflammation, thought to be preceded by Nurr1 LBD SUMOylation, is believed to protect surrounding cells such as DA neurons from potentially damaging inflammatory mediators (Saijo et al., 2009). Nurr1 has many reported splice variants found in the human brain. However one of particular interest, termed Nurr-1a, is reported to have truncated LBD whilst retaining an intact AF-1; previously described as the key region for transcriptional regulation in NR42 nuclear receptors (Michelhaugh et al., 2005, Ichinose et al., 1999, Maxwell and Muscat, 2006). Albeit the function of Nurr-1a remains to be investigated. Fully understanding the mechanisms in which Nurr1 regulates the expression of key neuronal and inflammatory genes, and any role Nurr-1a may or may not have in these processes, will help to clarify, or reveal targets for therapeutic manipulation in diseases with a neuroinflammatory component such as Parkinson’s Disease. Therefore, this work aimed to clarify the mechanisms surrounding Nurr1 and Nurr-1a SUMOylation, and the effect this may have on gene transcription. Whilst also focusing on the development of human based neuronal and inflammatory models which can better recapitulate diseases with a neuroinflammatory factor.